Impact of changes in fat mass and lean soft tissue on bone mineral density accrual in adolescents engaged in different sports: ABCD Growth Study - Luiz-de-Marco, Rafael [UNESP]; Gobbo, Luis Alberto [UNESP]; Castoldi, Robson Chacon [UNESP]; Maillane-Vanegas, Santiago [UNESP]; da Silva Ventura Faustino-da-Silva, Yuri [UNESP]; Exupério, Isabela Neto [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Fernandes, Romulo A. [UNESP] (Springer Nature, 2020)
Summary: Body composition can have a significant impact on bone mineral density (BMD) in pediatric patients and may cause bone disease. This study demonstrated that lean soft tissue (LST) seems to have a greater impact on BMD gain in the lower limbs of adolescents. Purpose: To analyze the impact of changes in lean soft tissue (LST) and fat mass on areal bone mineral density (BMD) accrual in the lower limbs among adolescents engaged in sports with different weight-bearing levels. Methods: Longitudinal (12 months: measurements at two time points). Adolescents of both sexes (n = 191; 62 girls [32.5%] and 129 boys [67.5%]) were divided into three groups: control group (n = 65), swimming group (n = 25), and weight-bearing sports group (n = 100). Absolute changes in LST (kg) and fat mass (kg) were the independent variables, while BMD accrual (left and right legs) was the dependent variable. Linear regression was used to assess the relationship between dependent and independent variables in a multivariate model adjusted by sex, body weight, somatic maturation, serum osteocalcin, and baseline values of BMD of the lower limbs. Results: For the left leg, LST was positively related to areal BMD accrual in the control (β = 0.021 [95%CI: 0.001 to 0.042]) and weight-bearing sport groups (β = 0.051 [95%CI: 0.037 to 0.065]), but not among swimmers (β = 0.029 [95%CI: − 0.004 to 0.062]). For the right leg, LST was positively related to areal BMD accrual in the swimming group (β = 0.065 [95%CI: 0.031 to 0.100]) and weight-bearing sport groups (β = 0.048 [95%CI: 0.034 to 0.062]), but not in the control group (β = 0.014 [95%CI: − 0.002 to 0.030]). Fat mass was not significantly related to areal BMD in either leg. Conclusions: Changes in LST were the most relevant determinant of BMD accrual in the lower limbs, mainly among adolescents engaged in sports.
Keywords: Adolescents; Bone health; Sports